Begoso cabin : a Pecos country retreat - Graña, Mari, 1936- (University of New Mexico Press, 1999)
"Mari Grana begins her account of an adventure that grew out of her desire to withdraw to the wild and that ends with a sense of homecoming and community: "I saw over a rise in a meadow a little stone cabin far in the distance. The landscape of the canyon - the rocky pine-covered ridges, the long wide meadow with the escarpment of Rowe Mesa rising in the background - suddenly became the place I had dreamed about.""--Jacket